2015
DOI: 10.1002/2015gl066293
|View full text |Cite
|
Sign up to set email alerts
|

Tropical sources and sinks of carbonyl sulfide observed from space

Abstract: According to current budget estimations the seasonal variation of carbonyl sulfide (COS) is governed by oceanic release and vegetation uptake. Its assimilation by plants is assumed to be similar to the photosynthetic uptake of CO2 but, contrary to the latter process, to be irreversible. Therefore, COS has been suggested as cotracer of the carbon cycle. Observations of COS, however, are sparse, especially in tropical regions. We use the comprehensive data set of spaceborne measurements of the Michelson Interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
110
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(121 citation statements)
references
References 51 publications
9
110
2
Order By: Relevance
“…Their results implied a large ocean OCS source over the Indo-Pacific region, and the total ocean source budget was consistent with the global budget proposed by Berry et al (2013). A similar conclusion was obtained by Glatthor et al (2015), who showed that the OCS global seasonal cycle observed by MIPAS was more consistent with the seasonal cycles modeled using the Berry et al global 15 budget than using the global budget proposed earlier by Kettle et al (2002).…”
Section: Top-down Global Ocs Budgetsupporting
confidence: 73%
See 1 more Smart Citation
“…Their results implied a large ocean OCS source over the Indo-Pacific region, and the total ocean source budget was consistent with the global budget proposed by Berry et al (2013). A similar conclusion was obtained by Glatthor et al (2015), who showed that the OCS global seasonal cycle observed by MIPAS was more consistent with the seasonal cycles modeled using the Berry et al global 15 budget than using the global budget proposed earlier by Kettle et al (2002).…”
Section: Top-down Global Ocs Budgetsupporting
confidence: 73%
“…A missing source of about 600-800 Gg S yr -1 in the atmospheric budget of OCS has recently been 15 identified by several top-down approaches (Berry et al, 2013;Glatthor et al, 2015;Kuai et al, 2015;Wang et al, 2016). Satellite data have shown that tropospheric OCS is elevated above the North Indian and northwest tropical Pacific oceans, and inverse models using enhanced oceanic emissions reproduced a similar pattern (Kuai et al, 2015).…”
Section: Oceanmentioning
confidence: 99%
“…The MIPAS OCS data set has already been presented in Glatthor et al (2015a), but focused on the signatures of tropical sources and sinks at the 250 hPa level only. In this paper we will give a more global overview of this data set.…”
mentioning
confidence: 99%
“…Recent work by Glatthor et al (2015) and Berry et al (2013) has shown that there should be a noticeable depletion of OCS over the Amazon and Congo rainforest areas due to strong vegetative uptake. This is indeed what is observed in these data, especially for the observations made during the day (Fig.…”
Section: Estimates Over Landmentioning
confidence: 99%
“…In retrospective analysis, Glatthor et al (2015) used the limb-viewing Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) instrument to retrieve OCS concentrations at the lowermost detectable level, 250 hPa, using standard optimal estimation techniques. The compiled results from 2002 to 2012 in 5 • by 15 • latitude-longitude bins showed clear evidence of elevated ocean sources and tropical rainforest sinks that vary with season.…”
Section: Previous Estimates From Satellitementioning
confidence: 99%